Live to Work or Work to Live? An Age-Moderated Mediation Model on the Simultaneous Mechanisms Prompted by Workaholism Among Healthcare Professionals - Dordoni, Paola; Kraus-Hoogeveen, Sascha; Van Der Heijden, Beatrice I. J. M.; Peters, Pascale; Setti, Ilaria; Fiabane, Elena (Frontiers in Psychology, 2019)
The ‘ageing population’ implies an increased proportion of older professionals and a growing demand for healthcare services. Healthcare professionals are often highly committed to their work which can be reflected in high levels of workaholism, being a double-edged sword that can prompt both positive and negative mechanisms, differently affecting younger and older healthcare workers. The present study aims to gain insights into the relationships between healthcare professionals’ age, workaholism and job satisfaction, by estimating the sequential mediating roles of workload perceptions and emotional exhaustion. We used original survey data, including information on 750 healthcare professionals. Overall, the negative relationship between workaholism and job satisfaction was shown to be sequentially (and partially) mediated by workload perceptions and emotional exhaustion. Multi-Group SEM analyses revealed differences across three age groups (under 35; between 35 and 50; over 50). Only in the two younger age groups, we found a direct and positive relationship between workaholism and job satisfaction. In all age groups, we found the negative relationship between workaholism and job satisfaction to be sequentially (and partially) mediated by workload perceptions and emotional exhaustion. The indirect effects were relatively stronger in the younger age group. Workaholism can prompt both a ‘gain spiral’ and ‘a loss spiral’ among healthcare professionals. The first reflects workaholism to function as a job resource fostering job satisfaction (only for the two younger age groups). The second reflects workaholism to function as a job demand reducing job satisfaction. This mechanism was shown to be stronger with an increasing age.